\( B=p+5 \) and \( A=p^{2}+10 p+1 \), find an expression that equals \( 2 B+3 A \) in standard form
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
Let's start by substituting the expression for \( B \) into \( 2B \): \[ 2B = 2(p + 5) = 2p + 10 \] Next, we'll expand the expression for \( A \): \[ 3A = 3(p^2 + 10p + 1) = 3p^2 + 30p + 3 \] Now we can combine \( 2B \) and \( 3A \): \[ 2B + 3A = (2p + 10) + (3p^2 + 30p + 3) \] Combining like terms, we get: \[ 2B + 3A = 3p^2 + (2p + 30p) + (10 + 3) = 3p^2 + 32p + 13 \] Thus, the expression that equals \( 2B + 3A \) in standard form is: \[ \boxed{3p^2 + 32p + 13} \]